Thermokinetic decomposition and sensitivity studies of 4, 4ˊ-diamino-3, 3ˊ-azoxy furazan (DAAF)-based melt cast explosive formulations. Issue 3 (3rd July 2018) - Badgujar, Dilip M.; Talawar, Mahadev B.
ABSTRACT: 4, 4ˊ-diamino-3, 3ˊ-azoxy furazan (DAAF) is an insensitive high explosive. DAAF has safety characteristics (impact, friction) similar to triaminotrinitrobenzene and shock sensitivity similar to HMX. The present article describes the thermal analysis and sensitivity study of DAAF with RDX and 2, 4, 6-trinitrotoluene (TNT). DAAF has been evaluated as a possible replacement for RDX in TNT-based, aluminized as well as nonaluminized melt cast formulation. DAAF-based melt cast formulations were characterized for their sensitivity to mechanical stimuli, bomb calorimetric analysis, and thermal decomposition behavior. The thermal analysis reveals the compatibility of DAAF with benchmark explosives like RDX and TNT in explosive formulations. The composition DT (DAAF + TNT) and DTA (DAAF + TNT+ Al) is more friction and impact insensitive as compared to RT (RDX + TNT) and RTA (RDX + TNT+ Al) compositions. The bomb calorimetric values of DT composition as well as DTA composition are higher than RT and RTA compositions. The result shows that DAAF can be effectively used as a RDX replacement in melt cast explosive formulations. DT-based aluminized composition showed more thermal stability than RT- and RTA-based control compositions, which clearly revealed the usefulness of DAAF for enhanced blast effect.